The Assessment of Alternative Low-Cost Construction Materials and Techniques for Wall Structure - Mohd Satar, Nur Haziqah Aina; Ismail, Lokman Hakim (Recent Trends in Civil Engineering and Built Environment, 2023)
This thesis reviews the different types of currently practiced low-cost alternative construction materials and techniques used for wall structure. In recent years, rising construction costs have become a major source of concern for the construction sector. Costs of materials and machinery are two elements that contribute to the raise in construction costs. Construction professionals have suggested that using alternate building materials and methods is one way to reduce construction costs. However, there is a lack of studies and application in Malaysia regarding this topic. To address this need in Malaysia, this study is carried out to determine which alternatives will be suited to be implemented in Malaysia. The method to conduct this research is through case study based on past research by other researchers related to the topics of low-cost alternative building materials and techniques for wall structure. According to the findings of the case study, low-cost materials can be divided into two categories: natural materials and manmade materials. The materials and methods that are reviewed in this research are Rat Trap Bond, Cellular Lightweight Concrete Brick, Fly Ash Brick, Bamboo based walls, and Rice straw and husk. These materials can be used as alternative materials to build walls and other building structures. The cost, properties, and advantages are studied and are analyzed in the end of this research. Through adopting cost-effective, innovative and environmentally friendly technology it will raise many advantages not only to the construction sector but also to society.